Low density polyethylene composites reinforced with Australian King Palm fibers: mechanical and thermal properties - Mulinari, Daniella R.; Guedes, Júlia Rocha; Simba, Bruno Galvão [UNESP] (Springer Nature, 2017)
The aim of this work is to obtain and evaluate the mechanical and thermal properties of low Density Polyethylene (LDPE) composites reinforced with fibers from Australian King Palm fibers. Raw fibers were characterized by X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) Spectroscopy. The chemical composition of the fibers was also evaluated. After characterizing the fibers were mixed into the LDPE, in proportions of 5, 10, 15 and 20% (wt/wt) using a thermokinetic mixer model MH-50H. Furthermore tensile, flexural and impact specimens were prepared for evaluation of mechanical properties. The composites were analyzed through SEM micrographs of fractured surfaces and thermal analysis. The results indicate that the reinforcement decreases the thermal stability of the composites, but caused an increase the mechanical properties of the composites. The composites reinforced with of raw fibers 20% (wt/wt) showed significant increase in the tensile strength, flexural and impact.
Keywords: Composites; LDPE; Mechanical properties; Palm fibers; Thermal mechanical